Analisis Konsep Transparansi dalam Pelaporan Keuangan Syariah Terhadap Kepercayaan Stakeholder - Armach Dwy Syahbani; Azkiah Bafdah; Ferdiansyah Ferdiansyah; Masyhuri Masyhuri (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to analyze the concept of transparency in Islamic financial reporting and its impact on stakeholder trust in Islamic financial institutions. Transparency is understood as the presentation of financial information that is open, accurate, honest, and in accordance with Islamic principles, thus reflecting institutional accountability. In practice, Islamic financial reporting serves not only as a means of conveying economic information but also as a form of moral and spiritual accountability to the community. This study uses a qualitative approach through a literature review, examining various theories, regulations, and research findings related to transparency in Islamic financial reporting. The results show that consistent implementation of transparency can increase institutional credibility, strengthen relationships with stakeholders, and foster sustainable trust. Conversely, a lack of information disclosure has the potential to undermine stakeholder confidence in the institution's integrity and performance. Therefore, transparency in Islamic financial reporting is a crucial element in maintaining the reputation, accountability, and sustainability of Islamic financial institutions amidst the development of the modern economic system.